ProjectorKit: Easing rapid prototyping of interactive applications for mobile projectors - WEIGEL, Martin (Institutional Knowledge at Singapore Management University, 2013)
Researchers have developed interaction concepts based on mobile projectors. Yet pursuing work in this area— particularly in building projector-based interactions techniques within an application—is cumbersome and timeconsuming. To mitigate this problem, we contribute ProjectorKit, a flexible open-source toolkit that eases rapid prototyping mobile projector interaction techniques.